Feeding preference of Eurasian beavers (Castor fiber) in the Lower Rhine region, Germany - Margarete Dytkowicz; William M. Megill; Tillmann K. Buttschardt (Academia Environmental Sciences and Sustainability)
Eurasian beavers (Castor fiber) have been successfully reintroduced into the wild in many European countries. Because of the growth of populations and the associated spread, more and more areas in nature are being occupied that have not previously been checked by humans with regard to their quality. One such area that has been taken over by beavers is the district of Kleve, North-Rhine Westphalia, Germany. In this study, the variables of habitat selection were analyzed. For this purpose, eight habitats occupied by beavers in the district of Kleve were analyzed. These included both artificial and natural water bodies, as well as nature reserves and non-protected areas. Seven of the eight habitats examined had sufficient biodiversity indices. The highest value was measured in a natural water body in a nature reserve (H = 2.51), and the lowest value was measured in an artificial, unprotected habitat (H = 0.15). Food choice preferences were consistent with observations from previous studies, indicating that all habitat requirements in relation to trees are met.